Outcome of Listing for Cardiac Transplantation for Failed Fontan - Daniel Bernstein; David C. Naftel; Clifford Chin; Linda J. Addonizio; P. Gamberg; Elizabeth D. Blume; Daphne T. Hsu; Charles E. Canter; James K. Kirklin; W. Robert Morrow (2006)
Background— The Fontan procedure is a successful palliation for children with single-ventricle physiology; however, many will eventually require heart transplantation. The purpose of this study was to determine risk factors for death awaiting transplantation and to examine results after transplantation in Fontan patients. Methods and Results— A retrospective, multi-institutional review was performed of 97 Fontan patients <18 years of age listed at 17 Pediatric Heart Transplant Study centers from 1993 to 2001. Mean age at listing was 9.7 years (0.5 to 17.9 years); 25% were <4 years old; 53% were United Network for Organ Sharing status 1; 18% required ventilator support. Pretransplantation survival was 78% at 6 months and 74% at 12 months and was similar to 243 children with other congenital heart disease (CHD) and 747 children without congenital heart disease (No-CHD), who were also awaiting transplantation. Patients who were younger, status 1, had shorter interval since Fontan, or were on a ventilator were more likely to die while waiting. At 6 months, the probability of receiving a transplant was similar for status 1 and 2 (65% versus 68%); however, the probability of death was higher for status 1 (22% versus 5%). Seventy patients underwent transplantation. Survival was 76% at 1 year, 70% at 3 years, and 68% at 5 years, slightly less than CHD and No-CHD patients. Causes of death included infection (30%), graft failure (17%), rejection (13%), sudden death (13%), and graft coronary artery disease (9%). Protein-losing enteropathy (present in 34 patients) resolved in all who survived >30 days after transplantation. Conclusions— Heart transplantation is an effective therapy for pediatric patients with a failed Fontan. Although early posttransplantation survival is slightly lower than other patients with CHD, long-term results are encouraging, and protein-losing enteropathy can be expected to resolve.